Bentuk Ganti Rugi atas Penyalahgunaan Kartu Atm oleh Pendamping Program Keluarga Harapan Perspektif Wahbah Az Zuhaili di Kota Tanjungbalai - Sirait, Sri Wardani; Tarigan, Tetty Marlina (Universitas Ekasakti, 2023)
The Family Hope Program, hereinafter abbreviated as PKH, is cash assistance that is channeled through ATMs to make it easier for residents, but this has a low level of security so that it can harm residents as experienced by residents of Environment VII, Semulajadi Sub-District, Tanjungbalai City. The purpose of this study was to find out the arrangements for misusing other people's ATMs, the implementation and distribution of PKH in environment VII Semulajadi Village, Tanjungbalai City, and forms of compensation for ATM card misuse from the perspective of wahbah az zuhaili. This study uses field research methods (field research). This research is descriptive qualitative in nature. Data collection was carried out by means of interviews, observation and existing literature. Research results show that there is a discrepancy between the implementation and distribution of PKH between the field and regulations and according to Wahbah Az Zuhaili, the form of compensation for ATM card misuse is to compensate for losses in a similar form and the compensation requested by victims from PKH assistants is not in accordance with Wahbah Az Zuhaili's opinion regarding there are additional costs.